Relationship between Gadget Usage and Cognitive Development of Preschool - Putri, Angeli Soradin; Hendrawati, Sri; Kosim, Kosim (GLOBAL HEALTH SCIENCE GROUP, 2024)
Approximately 79% of Indonesian children have used gadgets. Such use can have an impact on child development at preschool age, especially cognitive development. At the golden age, children experience 80% brain development which makes it easy for children to absorb information that occurs around them. Cognitive is the way children adapt and define objects and events in their environment. The purpose of this study is to identify patterns of gadget use, identify cognitive development, and identify the relationship between gadget use and cognitive development of preschool children at Kemala Bhayangkari 43 Jatinangor Kindergarten. Method: This research is quantitative with a correlational approach and uses a total sampling method of 34 respondents at Kemala Bhayangkari 43 Jatinangor Kindergarten. The measuring instrument used is the Gadget Use Pattern instrument in children with a validity value of 0.388 and a reliability of 0.666 and the Preschool Child Cognitive Development instrument (5-6 Years) with a validity value above 0.4 and a reliability result of 0.780 which means that these two instruments are valid and reliable. Data analysis used in this study used univariate and bivariate analysis with fisher's extract test. Results: The results of the univariate test on gadget use in children fall into the quite good category with the results of 23 respondents (67.6%) and cognitive development in children falls into the good category with the results of 25 respondents (73.5%). The bivariate test results using fisher's extract test with sig. (2-tailed) is 0.670 (>0.05). Conclusions: Based on the results of this study, it can be concluded that there is no relationship between the use of gadgets and the cognitive development of preschool children (5-6 years old) at Kemala Bhayangkari 43 Jatinangor Kindergarten.